Turbulent wall shear stress measurement in aqueous solutions containing poly(ethylene oxide) and hexadecyltrimethylammonium choride complexes - Siriluck Suksamranchit (Chulalongkorn University, 2014)
Thesis (Ph.D.)--Chulalongkorn University, 2006